Determination of attribution-sport performance pattern among school level netball players - Sukiman, Norazlinda (Universiti Sains Malaysia, 2014)
The present study was undertaken with an objective to determine the attribution sport performance pattern among school level netball players after winning and losing a match. Twenty four physically healthy female school athletes aged from 13 to 17 from Sekolah Menengah Kebangsaan Putera were recruited to participate in this study. The participants consisted of netball players that represent the school in the state competition. Modified version of the revised Causal Dimension Scale-II (CDS-II; McAuley, Duncan, & Russell, 1992) was used in this study to assess the attribution-sport performance pattern immediately after the match. The CDS-II allows the participants to make causal attributions about an event along four causal dimensions: (a) Locus of causality (internal-external), (b) Stability (stable-unstable), (c) Personal control (personally controllable-not personally controllable) and (d) External control (controllable by others-not controllable by others). Participants first responded to a question regarding their opinion regarding their performance in the match with the team. The participants then answered 12 questions related to the dimensional properties of their attribution. Responses were made by circling a number on a 9-point Likert scale ranging from 1 (strongly unrelated to you) to 9 (strongly related to you). The questionnaire was administered four times. Repeated measure ANOVA was used to analyze the data. The result of the study revealed that the participants attributed their successful performances to external, unstable and uncontrollable causes and they attributed their least successful performance to internal, stable and controllable causes. There was a significant difference (p 0.05) between the attributions all participants gave for winning and losing the match focus of causality dimension. While there were no significant differences (p 0.05) found in the other dimensions. In conclusion, it is seen that female school level netball players attribute outcomes to external, unstable and uncontrollable causes when winning the match.